Helenalin Analogues Targeting NF‐κB p65: Thiol Reactivity and Cellular Potency Studies of Varied Electrophiles. (19th January 2018) - Widen, John C.; Kempema, Aaron M.; Baur, Jordan W.; Skopec, Hannah M.; Edwards, Jacob T.; Brown, Tenley J.; Brown, Dennis A.; Meece, Frederick A.; Harki, Daniel A.
Abstract: Helenalin is a pseudoguaianolide natural product that targets Cys38 within the DNA binding domain of NF‐κB transcription factor p65 (RelA). Helenalin contains two Michael acceptors that covalently modify cysteines: a α‐methylene‐γ‐butyrolactone and a cyclopentenone. We recently reported two simplified helenalin analogues that mimic the biological activity of helenalin and contain both electrophilic moieties. To determine the individual contributions of the Michael acceptors toward NF‐κB inhibition, we synthesized a small library of helenalin‐based analogues containing various combinations of α‐methylene‐γ‐butyrolactones and cyclopentenones. The kinetics of thiol addition to a subset of the analogues was measured to determine the relative thiol reactivities of the embedded electrophiles. Additionally, the cellular NF‐κB inhibitory activities of the analogues were determined to elucidate the contributions of each Michael acceptor to biological potency. Our studies suggest the α‐methylene‐γ‐butyrolactone contributes most significantly to the NF‐κB inhibition of our simplified helenalin analogues. Abstract : Sesquiterpenes simplified : A library of small molecules containing α‐methylene‐γ‐butyrolactones and/or cyclopentenones representative of the natural product helenalin was synthesized. The kinetics of hetero‐Michael addition of thiols to each electrophile was characterized, as well as the abilities of each compound to regulate NF‐κB signaling. We find the α‐methylene‐γ‐butyrolactone reacts irreversibly with biological thiols and contributes most to biological activity amongst the two electrophiles.